PELATIHAN PENULISAN SURAT RESMI DENGAN KONSEP ANDRAGOGI PADA APARATUR DESA DI KECAMATAN PAMEUNGPEUK KABUPATEN GARUT TAHUN 2018 - lina Siti Nurwahidah; Zoni Sulaiman; Ari Kartini; Ardi Mulyana; cecep Dudung Julianto (Lembaga Pengabdian kepada Masyarakat Institut Pendidikan Indonesia Garut, 2018)
Letters are one of the written communication media used in interaction. In writing letters, especially formal letters, it is not just the contents of the letter that must be considered, but other supporting aspects must also be considered, such as the form of letters and letter editors regarding the use of diction, spelling, and effective kalimsat. During this time, there are still many government and private employees at the lower levels who do not yet know the procedures for writing official letters that meet standard standards. They only make letters by copy and paste from the previous letter examples. They do not have special knowledge and guidelines in making official letters. This is evident from the results of an error analysis in an official letter made by the village apparatus in the Pameungpeuk sub-district of Garut district. The analysis showed that there were inconsistencies in the use of letter forms and letter editor errors including the use of diction, spelling, and effective sentences. In connection with this problem, a formal letter writing training was conducted with the concept of andragogy in the village apparatus in the Pameungpeuk sub-district of Garut district. The training results showed an increase in knowledge and practice in making official letters in accordance with the standard rules for writing formal letters.